Enhancing insulin sensitivity in type 2 diabetes mellitus using apelin-loaded small extracellular vesicles from Wharton’s jelly-derived mesenchymal stem cells: a novel therapeutic approach - Jing Cui; Mingkun Wang; Wenhong Zhang; Jiachen Sun; Yan Zhang; Li Zhao; Zhibo Hong; Dongtao Li; Yi Xiong Huang; Ningkun Zhang; Yu Chen (Diabetology & Metabolic Syndrome, 2024)
Abstract Background Type 2 diabetes mellitus (T2DM), characterized by β-cell dysfunction and insulin resistance (IR), presents considerable treatment challenges. Apelin is an adipocyte-derived factor that shows promise in improving IR; however, it is limited by poor targeting and a short half-life. In the present study, engineered small extracellular vesicles (sEVs) derived from Wharton’s jelly-derived mesenchymal stem cells (WJ-MSCs) loaded with apelin were used to address the limitations of the therapeutic application of apelin. Methods WJ-MSCs were transduced to obtain engineered sEVs loaded with overexpressed apelin (apelin-MSC-sEVs) and the control sEVs (MSC-sEVs). T2DM mice were injected with apelin-MSC-sEVs and MSC-sEVs, and blood glucose monitoring, glucose and insulin tolerance tests, confocal microscopy, and immunocytochemical analysis were performed. IR models of 3T3-L1 adipocytes were employed to detect GLUT4 expression in each group using western blotting; the affected pathways were determined by measuring the changes in Akt and AMPK signaling and phosphorylation. Results Upon successful engineering, WJ-MSCs demonstrated significant overexpression of apelin. The genetic modification did not adversely impact the characteristics of sEVs, ranging from surface protein markers, morphology, to particle size, but generated apelin-overexpressed sEVs. Apelin-MSC-sEVs treatment resulted in notable enhancement of Akt and AMPK pathway activities within 3T3-L1 adipocytes and adipose tissues of T2DM mice. Furthermore, the apelin-loaded sEVs significantly reduced plasma glucose levels, increased pancreatic β-cell proliferation, improved insulin and glucose tolerance, and modulated pro-inflammatory cytokine profiles, compared to mice treated with the control sEVs. Conclusion Our study developed novel genetically engineered apelin-loaded sEVs derived from WJ-MSCs, and demonstrated their potent role in augmenting insulin sensitivity and regulating inflammatory responses, highlighting their therapeutic promise in T2DM management. The findings open new avenues for the development of clinically viable treatments for T2DM in humans using the apelin-loaded sEVs.